Dažādu mācību metožu lietojuma iespējas sociokultūras kompetences veidošanai folkloras apguves procesā mazākumtautību izglītības programmas 5.klasē - Muska, Līvija (Latvijas Universitāte, 2007)
Diplomdarbā „Dažādu mācību metožu lietojuma iespējas sociokultūras kompetences veidošanai folkloras apguves procesā mazākumtautību izglītības programmas 5.klasē” akcentēti sekojoši jautājumi: •teorētiskās literatūras analīze; •pusaudžu vecuma īpatnību ievērošana, mācot latviešu valodu; • ieskats dažādās mācību teorijās; •mācību stundas struktūra, analīze, vērtēšana; •dažādu metožu praktiskā pielietošana latviešu valodas stundās; •didaktiskā modeļa „Mārtiņdiena” izstrāde; •darba procesā gūto rezultātu analīze. Diplomdarba mērķis - parādīt, ka, izmantojot dažādas mācību metodes, var veicināt sociokultūras kompetences pilnveidošanu folkloras apguvē 5.klasē.

The title of the Diploma Paper is “Possibilities of Using Different Methods in Developing Pupils’ Socio-cultural Competence in the Acquisition of Folklore in Grade 5 of Minority Educational Programme”. The following items have been emphasized in the Paper: •analysis of the theoretical literature; •observation of the teenager peculiarities when teaching the Latvian language; •insight into different teaching theories; •structure, analysis and assessment of the lesson; •practice of different methods during lessons of the Latvian language; •development of the didactic model “Mārtiņdiena” (Martin’s Day); •analysis of the results acquired during the work process. The aim of the Diploma Paper is to show that by application of different teaching methods it is possible to facilitate the development of socio-cultural competence in learning folklore in form 5.
Possibilities of using different methods in developing pupils’ socio-cultural competence in the acquisition of folklore in Grade 5 of minority educational program
Keywords: Pedagoģija